Meningkatkan Kemandirian Anak Usia Dini Melalui Metode Bermain Peran RA - Erniyanti , Laksmi; Shovi Yatul Istifadah; Andi Wapa (Gayaku Publisher, 2025)
This study was conducted based on the problems that occurred in group B of early childhood children who were categorized as having low child independence. Therefore, this study aims to increase the independence of children in group B. The method that is considered to be able to provide an increase in children's independence is by using role play. This study uses a classroom action research method conducted at RA Baitun Najah. Data collection is carried out through observation by paying attention to the observation indicators of children's independence. The results of this study using the role play method were carried out in two cycles, so that the role play method was carried out by paying attention to the conditions of children in group B of RA Baitun Najah. So that when this learning cycle was carried out as many as two cycles, it can be concluded that the use of the role play method provided a significant increase in the effect of Children's Independence in Pre-Cycle: 38.5%, Cycle I: 64.25%, Cycle II: 84.75%.